Increasing Impulsive Buying Through Sales Promotions Among TikTok Shopee Users (A Case Study on TikTok Shopee E-Commerce) - Anita Anggraini Manurung; Heru Sulistyo (Komunitas Dosen Indonesia, 2026)
This study aims to examine the effect of sales promotion on impulsive buying among TikTok Shop users, with shopping motivation as a moderating variable. The rapid growth of social commerce has encouraged businesses to intensively use sales promotions such as discounts, free shipping, and flash sales, which can trigger unplanned purchasing behaviour. This research employs a quantitative approach using a survey method conducted on TikTok Shop users who have previously made purchases. The sample was selected through purposive sampling, and the data were analysed using the Partial Least Square (PLS) method with the assistance of SmartPLS software. The results indicate that sales promotion has a positive and significant effect on impulsive buying. Furthermore, shopping motivation is proven to moderate the relationship between sales promotion and impulsive buying, strengthening the impact of promotional activities on consumers with higher shopping motivation. This study contributes to consumer behaviour literature and provides practical insights for businesses in designing effective promotional strategies on TikTok Shop.